A Scientometrics Analysis of Publications of AIIMS and PGIMER during 2000-2019 - Singhal, Madhuresh; Dhanamjaya, M. (Journal of Information and Knowledge, 2021)
The objective of this article is to analyze and compare the scientometric parameters of the journal publications of 2 top Indian medical research institutes – All India Institute of Medical Sciences (AIIMS) and Post Graduate Institute of Medical Education and Research (PGIMER). The data set was collected using the Web of Science (WoS) database for 20 years (2000-2019). We have compared the number of journal publications and citations for these two institutions. We used various bibliometric parameters like the number of articles, the number of citations received, average impact factor, international collaborations, and authorship pattern to analyze the research contributions made by the authors of both institutes. The data reveals that AIIMS published 20,550 articles in 2382 unique journals with 1,48,388 citations, and PGIMER published 13,142 articles in 1695 unique journals with 69,659 citations. Most of the articles were published in peer-reviewed international journals having a high impact factor. The average number of citations received per article is 7.22 for AIIMS and 5.30 for Post Graduate Institute of Medical Education and Research (PGIMER).